Table of contents
- 0. Functions7h 52m
- Introduction to Functions16m
- Piecewise Functions10m
- Properties of Functions9m
- Common Functions1h 8m
- Transformations5m
- Combining Functions27m
- Exponent rules32m
- Exponential Functions28m
- Logarithmic Functions24m
- Properties of Logarithms34m
- Exponential & Logarithmic Equations35m
- Introduction to Trigonometric Functions38m
- Graphs of Trigonometric Functions44m
- Trigonometric Identities47m
- Inverse Trigonometric Functions48m
- 1. Limits and Continuity2h 2m
- 2. Intro to Derivatives1h 33m
- 3. Techniques of Differentiation3h 18m
- 4. Applications of Derivatives2h 38m
- 5. Graphical Applications of Derivatives6h 2m
- 6. Derivatives of Inverse, Exponential, & Logarithmic Functions2h 37m
- 7. Antiderivatives & Indefinite Integrals1h 26m
3. Techniques of Differentiation
Basic Rules of Differentiation
Problem 59a
Textbook Question
{Use of Tech} Equations of tangent lines
Find an equation of the line tangent to the given curve at a.
y = −3x2 + 2; a=1
![](/channels/images/assetPage/verifiedSolution.png)
1
Step 1: Identify the function and the point of tangency. The function given is \( y = -3x^2 + 2 \) and the point of tangency is at \( x = a = 1 \).
Step 2: Find the derivative of the function to determine the slope of the tangent line. The derivative of \( y = -3x^2 + 2 \) with respect to \( x \) is \( y' = \frac{d}{dx}(-3x^2 + 2) = -6x \).
Step 3: Evaluate the derivative at \( x = 1 \) to find the slope of the tangent line at that point. Substitute \( x = 1 \) into \( y' = -6x \) to get the slope \( m = -6(1) = -6 \).
Step 4: Find the y-coordinate of the point of tangency by substituting \( x = 1 \) into the original function. \( y = -3(1)^2 + 2 = -3 + 2 = -1 \). So, the point of tangency is \( (1, -1) \).
Step 5: Use the point-slope form of a line to write the equation of the tangent line. The point-slope form is \( y - y_1 = m(x - x_1) \), where \( m \) is the slope and \( (x_1, y_1) \) is the point of tangency. Substitute \( m = -6 \), \( x_1 = 1 \), and \( y_1 = -1 \) into the equation to get \( y - (-1) = -6(x - 1) \).
Recommended similar problem, with video answer:
![](/channels/images/assetPage/verifiedSolution.png)
This video solution was recommended by our tutors as helpful for the problem above
Video duration:
4mPlay a video:
Was this helpful?
Watch next
Master Derivatives of Linear Functions with a bite sized video explanation from Callie
Start learningRelated Videos
Related Practice